PROFESSIONAL EXAMINATIONS: ACCOUNTING PRACTICE. - Chamberlain, John H. (The Accounting Review, 1961)
The article presents information on problems that were prepared by the Board of Examiners of the American Institute of Certified Public Accountants and were presented as the first halt of the C.P.A. examination in accounting practice on May 17, 1961. The candidates were required to solve all problems. One of the problems that was there in Accounting practice is discussed here. A company has hypothecated its accounts receivable with the bank under an agreement whereby the bank lends the company 80% on the hypothecated accounts receivable. Accounting for and collection of the accounts are performed by the company, and adjustments of the loan are made from daily sales reports and daily deposits. The bank credits the Distributors, Inc. account and increases the amount of till loan for 80% of the reported sales. The loan agreement states specifically that the sales report must be accepted by the bank before Distributors, Inc. is credited Sales reports are forwarded by Distributors, Inc. to the bank on the first day following the date of sales. The bank allocates each deposit 80% to the payment of the loan and 20% to Distributors, Inc. account. Thus, only 80% of each day's sales and 20% of each collection deposit are altered on the bank statement. Distributors, Inc. accountant records the hypothecation of new account to receivable value (80% of sales) as a debit to cash and a credit to the bank loan as of the date of sales. One hundred per cent of the collections on accounts receivable to recorded as a cash receipt; 80% of the collections is recorded in the cash disburse